CELEBRITY ENDORSER INTERVENING EFFECTS REGARDING THE DECISION TO PURCHASE UMRAH TRAVEL AGENCY SERVICES - Firmansyah Firmansyah; Malik Fajar Ardiansyah; Juliana Juliana; Yuana Tri Utomo; Erwin Permana; Ropi Marlina; Robbi Awaluddin (Accounting Department, Politeknik Negeri Bandung, 2026)
This study aims to show the influence of price, perceived value, celebrity endorser and religiosity on purchasing decisions for Umrah travel agency services with promotion as an intervening variable. The method used in this research is a quantitative descriptive method with the SEM-PLS analysis method. The analysis tool used was SmartPLS 4.0.9.3 with a sample size of 243 respondents using Google forms and distributed on social media. This research found that the price level and perceived value did not influence the decision to purchase Umrah travel agency services. Apart from that, the level of promotion, religiosity, and celebrity endorsers have a positive influence on purchasing decisions for Umrah travel agency services. Another finding is that the celebrity endorser variable does not mediate the price, perceived value and religiosity variables on purchasing decisions. Meanwhile, the celebrity endorser variable mediates the promotion variable on purchasing decisions for Umrah travel agency services.